Does Migrants' Consumption of Cultural Goods Impact on Their Economic Integration? Disclosing the Culture-to-Market Pathway - Salvatore Carrozzo; Elisabetta Lodigiani; Alessandra Venturini (Institute of Labor Economics (IZA), 2024)
The consumption of cultural goods can play a crucial role in the social and economic integration of immigrants into their destination country. In this paper, we investigate the effect of the cultural national program, IoStudio, designed to enhance the consumption of cultural goods among upper secondary students in Italy, on post-secondary investment in education and early labor market conditions among young immigrants. Using data from a unique survey conducted by the Institute for Multiethnic Studies (ISMU) on a representative sample of the entire immigrant population in the Italian Lombardy region and employing a difference-in-differences estimator, we find that the IoStudio policy has positive effects on investment in post-secondary education. Additionally, young foreigners exposed to the policy exhibit higher earnings, at least in the short run, when they enter the labour market. We claim that cultural consumption by immigrants is a relevant concern, deserving close attention in terms of increasing social capital and labour market inclusion.
Keywords: Z11; J61; J62; I26; 330; cultural participation; migrants; integration; Italy